Patterns of Co-Occurring Gray Matter Concentration Loss across the Huntington Disease Prodrome - Ciarochi, Jennifer Ashley; Calhoun, Vince D.; Lourens, Spencer; Long, Jeffrey D.; Johnson, Hans J.; Bockholt, H. Jeremy; Liu, Jingyu; Plis, Sergey M.; Paulsen, Jane S.; Turner, Jessica A.; , The PREDICT-HD Investigators; Coordinators of the Huntington Study Group (Frontiers in Neurology, 2016)
Huntington disease is caused by an abnormally expanded CAG trinucleotide repeat in the HTT gene. Age and CAG-expansion number are related to age at diagnosis, and can be used to index disease progression. However, observed onset-age variability suggests that other factors also modulate progression. Indexing prodromal (pre-diagnosis) progression may highlight therapeutic targets by isolating the earliest-affected factors. We present the largest prodromal Huntington disease application of the univariate method Voxel-based Morphometry, and the first application of the multivariate method Source-based Morphometry, to respectively compare gray matter concentration and capture co-occurring gray matter concentration patterns in control and prodromal participants. Using structural MRI data from 1050 (831 prodromal, 219 control) participants, we characterize control-prodromal, whole-brain gray matter concentration differences at various prodromal stages. Our results provide evidence for: (1) Regional co-occurrence and differential patterns of decline across the prodrome, with parietal and occipital differences commonly co-occurring, and frontal and temporal differences being relatively independent from one another, (2) Fronto-striatal circuits being among the earliest and most consistently affected in the prodrome (3) Delayed degradation in some movement-related regions, with increasing subcortical and occipital differences with later progression, (4) An overall superior-to-inferior gradient of gray matter concentration reduction in frontal, parietal, and temporal lobes, (5) The appropriateness of Source-based Morphometry for studying the prodromal Huntington disease population, and its enhanced sensitivity to early prodromal and regionally-concurrent differences.